The persistence of matching teaching and learning styles: A review of the ubiquity of this neuromyth, predictors of its endorsement, and recommendations to end it - Brown, Stephen B. R. E. (Frontiers in Education, 2023)
Educational neuroscience tries to bridge neuroscience and education. It tries to combat neuromyths: beliefs that appear grounded in neuroscientific research but that are not supported by empirical evidence. One such neuromyth claims that matching teaching style to students’ preferred learning styles (e.g. visual teaching to visual learning) will lead to improved academic outcomes. The only formal way to test this meshing hypothesis is by finding a statistical crossover interaction effect which shows that matching teaching and learning styles improves academic outcomes, while non-matching teaching and learning styles negatively affects academic outcomes (Pashler et al., 2008). Several studies are reviewed and none of these yielded empirical support for the meshing hypothesis. Reviewed studies suggest that educators widely believe the veracity of the meshing hypothesis. Predictive factors are discussed: even having some formal knowledge of neuroscience does not protect educators from endorsing neuromyths like the meshing hypothesis. A framework of focused neuroscience instruction for future educators is proposed.